1024 The Use of the Pedicled Anterolateral Thigh (ALT) Flap for the Reconstruction of Abdominal Wall Defects in High-Risk Patients: A Case Series and Systematic Review. (12th October 2021) - Newall, N; Jones, C; Ho, W; Curnier, A
Abstract: Introduction: The pedicled anterolateral thigh (ALT) flap is considered as a suitable option in complex abdominal wall reconstruction. Its use as a reconstructive option is infrequent in the literature, and to date, there has been no systematic review evaluating its long-term outcomes. We report our experience with the pedicled anterolateral thigh flap for abdominal wall reconstruction in high-risk patients. Method: A prospective database was created for patients with abdominal wall defects treated with pedicled ALT with extended fascia lata flaps between 2014 and 2017. Patient demographics, aetiology, size, location of defect and post-operative results were reviewed. Abdominal defects were classified into the following zones: 1A, upper midline; 1B, lower midline; 2, upper quadrant; 3, lower quadrant. A systematic review of the literature was conducted using PUBMED and EMBASE. Results: 4 patients (mean age 59.5 years, range 50-65 years) underwent reconstruction with pedicled ALT flaps. 3 flaps developed partial necrosis secondary to infection; 1 flap required surgical debridement, and 2 were managed conservatively. There was one flap failure, due to avulsion of the pedicle during inset. At mean follow up of 2.75 years (range 1 to 4 years) 3 patients have clinical bulging or herniation. Conclusions: Review of the literature demonstrated 52 patients from 17 case series or reports. The overall infection and partial flap loss rates were both 6%. There were no reported flap failures. Our study demonstrates that the pedicled anterolateral thigh flap is an effective flap option for the repair of large defects of the abdominal wall in high-risk patients.